2004
DOI: 10.1111/j.1365-2702.2004.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ‘person‐centred’ care: a new vision for gerontological nursing

Abstract: Currently considerable emphasis is placed on the promotion of person-centred care, which has become a watchword for good practice. This paper takes a constructively critical look at some of the assumptions underpinning person-centredness, and suggests that a relationship-centred approach to care might be more appropriate. A framework describing the potential dimensions of relationship-centred care is provided, and implications for further development are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
594
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(634 citation statements)
references
References 30 publications
19
594
0
6
Order By: Relevance
“…It is ethical in the sense that acknowledges the relevance of activities in this phase of life and context. This engagement, as revealed in the exemplars, could be enacted through small‐scale events within everyday activities, adding the acting dimension to care The understanding of influence illuminated in this study differs from conceptualizations of autonomy and decision‐making grounded in individualism, proposing a relational and acting understanding instead (Abma & Baur, 2015; Baur et al., 2013; Cardol et al., 2002; Ceci, Ttir, et al., 2013; Katz & Alegria, 2009; Nolan et al., 2004). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is ethical in the sense that acknowledges the relevance of activities in this phase of life and context. This engagement, as revealed in the exemplars, could be enacted through small‐scale events within everyday activities, adding the acting dimension to care The understanding of influence illuminated in this study differs from conceptualizations of autonomy and decision‐making grounded in individualism, proposing a relational and acting understanding instead (Abma & Baur, 2015; Baur et al., 2013; Cardol et al., 2002; Ceci, Ttir, et al., 2013; Katz & Alegria, 2009; Nolan et al., 2004). …”
Section: Discussionmentioning
confidence: 99%
“…More specifically, this framework makes explicit the need to move beyond technical competences and engage in the promotion of partnerships and collaborative practices with older adults (McCormack, 2004; McCormack & McCance, 2006). This relational perspective (Cardol, De Jong, & Ward, 2002; Nolan et al., 2004; Smebye & Kirkevold, 2013) also serves to counteract and problematize concepts such as autonomy, decision‐making, and self‐determination in person‐centered care, which assign a central value to individualism and cognitive competences (Boyle, 2008). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, our findings demonstrated that personality and value differences shaped these interdependent relationships between care stakeholders, particularly between adult children siblings, and between adult children and their parents (PwDs). We therefore encourage future research to examine the nature and quality of care relationships through relationship-centred frameworks which promote equitable, synergistic care relationships that reconcile the needs of all partners in care (Dupuis et al, 2012a; M. R. Nolan, Davies, Brown, Keady, & Nolan, 2004). Moreover, it is crucial that policy and services aim to be value-sensitive and flexible to accommodate a wide range of personalities, values, and care arrangements, from no adult child involvement to active care collaboration with multiple adult child siblings.…”
Section: Discussionmentioning
confidence: 99%
“…Resident-centred care is holistic and aims to satisfy the older individual’s needs, wishes and choices, provide individualized care, and strengthen his or her autonomy and self-determination (Brownie & Nancarrow, 2013; Li & Porock, 2014; McCormack et al, 2010; Morgan & Yoder, 2012; Yee et al, 1999). Resident-centred care concerns not just a relationship between a nurse or caregiver and an older person, but needs to be considered in a wider context of relations including, for instance, family, community, caring culture and, of particular relevance to this paper, the built or physical environment (McCormack & McCance, 2006; Nolan, Davies, Brown, Keady, & Nolan, 2004). This paper aims to contribute to the existing research by putting resident-centred care in a theoretical context of relationality and emergence (DeLanda, 2016).…”
Section: Introductionmentioning
confidence: 99%